Clinical Manifestations of Dengue in a Recent Outbreak in Muzaffarabad - Awan, Abdul Khalid; Ahmed, Imtiaz; Ahmed, Ashfaque; lone, Khusheed; Rafique, Robina; Haidri, Raza Manzoor; Riaz, Muhammad (International Journal of Pathology, 2018)
Objective: Assessment of clinical manifestations of dengue fever in area of Muzaffarabad during first everoutbreak of dengue fever.Design: Prospective, cross sectionalMaterial & Methods: Patients who were diagnosed as suffering from dengue fever were included in the study.Clinical manifestations of all patients were recorded in study Performa designed for the study. All routinelaboratory investigations including Blood complete examination including platelet counts, total leukocyte countand hematocrit, Blood Sugar, Urea, Creatinine, Serum Electrolytes, LFTS and Urine examination were performedin all patients. The diagnosis of dengue fever was confirmed with serological tests (NS1 Antigen or IgM/IgGAnti-dengue virus antibody titers).Results: In most patients, typical diagnostic clinical findings on physical examination were high fever (1020 to1040 F), suffused conjunctivae (45%) and facial flushing (82%) including external ears. The other prominentfeature was diffuse erythematous rash (18%) over extremities and truck. The early features at presentation werefacial flushing and suffused conjunctivae while rash appeared after 3-4 days of febrile illness in most patients.There was only small percentage (5%) of patients with insignificant cervical lymphadenopathy.Conclusion: Dengue fever has become an emerging significant health problem in our country. It is imperative tohave updated and sound knowledge of clinical manifestations of dengue fever, otherwise; many cases of denguefever will be misdiagnosed due to inappropriate assessment and misinterpretation of clinical signs andsymptoms.